PENGARUH KOMPENSASI FINANSIAL DAN IKLIM ORGANISASI TERHADAP KINERJA KERJA KARYAWAN PT. ARARA ABADI DISTRIK MERAWANG DESA PULAU MUDA KECAMATAN TELUK MERANTI KABUPATEN PELALAWAN - Pribadi, Panji; Marpaung, Rio; ', Marnis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at PT. Arara Abadi Merawang District village of Teluk Meranti Young Island Pelalawan. The samples in this study is numbered as many as 31 people. The analytical tool used was a questionnaire. the regression test Partially that each independent variables studied (Financial compensation and organizational climate) have an influence on the dependent variable (performance of employees). While the simultaneous regression test showed that the independent variables studied (financial compensation and climate organization) has a significant effect on the dependent variable (performance of employees). The magnitude of the effect caused by the two independent variables namely 51.4% while the remaining 48.6% influenced by other variables not examined in this study. The results of the testing that has been done, the t-test showed that each of the independent variables studied (financial compensation and climate organization) has a significant effect on the dependent variable (performance of employees). The dominant variable affecting the performance of employees at PT. Arara Abadi Merawang District Young Island village of Teluk Meranti Pelalawan is financial compensation where the value of the t-counted the highest compared with other independent variablesKeywords: Financial Compensation, Organizational Climate and Employee Performance